X-ray micrographic imaging system based on COTS CMOS sensors - Alcalde Bessia, Fabricio Pablo (2018)
This paper presents the use of commercial off the shelf CMOS image sensors for the acquisition of X-ray images with high spatial resolution. The X-ray images, with application in biology, electronic components inspection, and paleontology research, are obtained with 8-keV photons from a Cu tube. The quantum efficiency of the detector is estimated using attenuation lengths of photons in the sensor and compared to traditional scintillator conversion layers. The spatial resolution observed with the sensor is limited by the charge redistribution produced after photon interaction with Si.